THE USE OF LEARNING MEDIA IN ENHANCING STUDENTS’ LEARNING OUTCOMES THROUGH DISCOVERY LEARNING - Inayah, Lestiyani (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This research aims to improve the learning outcomes of students in class VIII I SMP Negeri 21 Semarang for the 2023/2024 academic year uses learning media. Study This is part of Classroom Action Research which uses cyclical components namely planning, implementation, observation, and reflection. Deep data collection techniques This research is an observation and a written test. The research was carried out in two cycles, namely, cycle 1 uses text-based learning media and cycle 2 uses media based on an interactive quiz application called Kahoot. The results of this research show that in cycle 1 the average student learning outcome was 82.8, while in cycle 2 obtained an average of 95.3. Based on these data it can be concluded that The use of learning media can improve the learning outcomes of class VIII I students SMP Negeri 21 Semarang.